A watch-and-wait approach for metachronous multiple colon cancer following neoadjuvant immunotherapy: a case report - Huang, Wang; Zhang, Shouru (Frontiers in Immunology, 2024)
The application of immunotherapy for treating colorectal cancer (CRC) is currently a research hotspot, and neoadjuvant immunotherapy has shown initial success in treating CRC. The watch-and-wait (W&W) approach is often used after achieving a clinical complete response (cCR) following preoperative treatment of low rectal cancer. However, thus far, the W&W approach has not been reported for patients with colon cancer. Here, we report the case of a 64-year-old patient with heterogeneous multigenic CRC who achieved cCR after five sessions of neoadjuvant immunotherapy before surgery. A W&W approach was used to spare the patient from surgery. A 64-year-old male presented with intermittent abdominal pain. A colonoscopy examination detected an irregular cauliflower-like mass near the hepatic flexure of the ascending colon. The biopsy results indicated adenocarcinoma of the ascending colon. The patient was administered pembrolizumab (200 mg, ivgtt, q3w). After one cycle of treatment, the intestinal obstruction symptoms disappeared, and the treatment was continued for additional three sessions. After complete clinical remission of the tumor was confirmed, the W&W approach was adopted. Follow-up CT scans and colonoscopy examinations confirmed no local tumor regeneration or metastasis. Neoadjuvant immunotherapy is effective for patients with DNA mismatch repair gene deficiency and/or microsatellite instability high with a high rate of cCR or pathologic complete response. The W&W approach may also be suitable for patients with colon cancer. The safety and feasibility of watch and wait in patients with colon cancer need to be verified by more clinical data.